THE FORMATION OF SLANG WORDS IN THE FILM PENYALIN CAHAYA - Kusumastuti, Tirta Salsabilla; Fawzi, Ary (ISLLAC : Journal of Intensive Studies on Language, Literature, Art, and Culture, 2023)
This research focuses on the formation of slang in the film Photocopier. This research is qualitative research with an orientation in the formation of slang words. The data collection used is in the form of listening techniques and note-taking techniques. Data analysis goes through four stages specifically, the process of data identification, data classification, data presentation, and data conclusion. The results of this study show that word formation can be done in four ways specifically, affixation, duplication, composition, and abbreviation. The meaning produced by word formation will vary depending on the existing context.